Penyuluhan Pelecehan Seksual Kepada Siswa-Siswi Kelas XII SMK Kartini Batam - Victor E D Palapessy; Alif Rahman Habibi (Jurnal Kabar Masyarakat, 2023)
This community service is carried out with the aim of helping students of SMK Kartini to understand and comprehend the impacts and dangers that can arise from sexual harassment. Sexual harassment is a serious issue that can endanger the mental and physical health of individuals, especially teenagers. Students of SMK (Vocational High School) belong to a vulnerable group at risk of experiencing sexual harassment. The community service method is implemented through collaboration between speakers, educators, and the school authorities. The first step is to identify issues related to sexual harassment that are relevant to the context of SMK students. Subsequently, appropriate and informative educational materials are developed based on comprehensive and responsible principles of sexual education. Then, the education is conducted through interactive sessions involving presentations, group discussions, case studies, and role-playing games. The educational materials cover understanding the definition of sexual harassment, types of sexual harassment, its impact on the health and well-being of students, prevention strategies, and how to report cases of sexual harassment. This community service is an important initial step in combating sexual harassment among the students of SMK Kartini. Continuous education and collaborative efforts among the school, families, and the community are necessary to create sustainable changes in behavior and attitudes towards sexual harassment. It is expected that the results of this community service will contribute positively to creating a safe, supportive, and harassment-free school environment for the students of SMK Kartini.